OSTEOLOGY OF THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA (CUVIER) - Gnanamuthu, J C (Indian Journal of Fisheries, 2011)
Rastrelliger kanagurta (the Indian Mackerel) is a fish of great commercial importance and of wide geographical distribution in the Indo-Pacific region. The study of the biology of the mackerel has been receiving considerable attention in this region during recent years. One of the important aspects of such work is the study on raciation. While the skeletal characters are of importance in such investigations, no standard description of the skeletal system of R. kanagurta or of any allied Indian species has been available so far for reference. It was therefore necessary to undertake a detailed study of the skeletal system of R. kanqgurta as a preliminary to studies on raciation in this species. The present paper deals with the osteology of the Indian mackerel.